Delayed Resolution of Feeding Problems in Patients With Congenital Hyperinsulinism - Worth, Chris; Hall, Caroline; Wilson, Sarah; Gilligan, Niamh; O'Shea, Elaine; Salomon-Estebanez, Maria; Dunne, Mark; Banerjee, Indraneel (Frontiers in Endocrinology, 2020)
Background Congenital Hyperinsulinism (CHI) is the most common cause of recurrent and severe hypoglycaemia in childhood. Feeding problems occur frequently in severe CHI but long-term persistence and rates of resolution have not been described. Methods All patients with CHI admitted to a specialist centre during 2015-2016 were assessed for feeding problems at hospital admission and for three years following discharge, through a combination of specialist speech and language therapy review and parent-report at clinical contact. Results Twenty-five patients (18% of all patients admitted) with CHI were prospectively identified to have feeding problems related to sucking (n=6), swallowing (n=2), vomiting (n=20) and feed aversion (n=17) at the time of diagnosis. Sixteen (64%) patients required feeding support by nasogastric/gastrostomy tubes at diagnosis; tube feeding reduced to 4 (16%) patients by one year and 3 (12%) patients by three years. Feed aversion resolved slowly with mean time to resolution of 240 days after discharge; in 15 patients followed up for three years, 6 (24%) continued to report aversion. The mean time (days) to resolution of feeding problems was lower in those who underwent lesionectomy (n=4) than in those who did not (30 vs 590, p=0.009). Conclusion Feeding problems, particularly feed aversion, are frequent in patients with CHI and require support over several years. By contrast, feeding problems resolve rapidly in patients with focal CHI undergoing curative lesionectomy, suggesting the association of feeding problems with hyperinsulinism.